2012
DOI: 10.1021/ac300040j
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Heat Pulses during PCR Extension Enabling Amplification of GC-Rich Sequences and Reducing Amplification Bias

Abstract: PCR amplification over GC-rich and/or long repetitive sequences is challenging because of thermo-stable structures resulting from incomplete denaturation, reannealing, and self-annealing of target sequences. These structures block the DNA polymerase during the extension step, leading to formation of incomplete extension products and favoring amplification of nonspecific products rather than specific ones. We have introduced multiple heat pulses in the extension step of a PCR cycling protocol to temporarily des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Nonetheless, most of these early assays were unable to amplify FM alleles reliably (Brown et al 1996; Chong et al 1994; Pergolizzi et al 1992; Saluto et al 2005; Tassone et al 2008). However, recent assays have been described that do enable large FM alleles to be detected reliably even in females and mosaic males (Chen et al 2010; Filipovic-Sadic et al 2010; Hayward et al 2016; Orpana et al 2012). These assays are all capable of amplifying even very large full mutation alleles with as many as 940 repeats.…”
Section: Dna-based Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, most of these early assays were unable to amplify FM alleles reliably (Brown et al 1996; Chong et al 1994; Pergolizzi et al 1992; Saluto et al 2005; Tassone et al 2008). However, recent assays have been described that do enable large FM alleles to be detected reliably even in females and mosaic males (Chen et al 2010; Filipovic-Sadic et al 2010; Hayward et al 2016; Orpana et al 2012). These assays are all capable of amplifying even very large full mutation alleles with as many as 940 repeats.…”
Section: Dna-based Assaysmentioning
confidence: 99%
“…The assay described by Filipovic-Sadic et al uses a commercially available product whose reagents are proprietory, so it is unclear what makes this assay work, although it was reported that more than 60 primer pairs and 1000s of buffer/additive combinations had to be tested before arriving at the optimal combination (Filipovic-Sadic et al 2010). The other assays make use of buffers that lack K + and include high concentrations of betaine, at least for very large alleles (Hayward et al 2016; Orpana et al 2012). Potassium ions stabilize the structures formed by the CGG-repeats (Usdin and Woodford 1995).…”
Section: Dna-based Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplification of genes of interest by PCR is an essential step in the study of their function and regulation, but DNA regions that are >60% GC require special PCR protocols due to their complex and strong secondary structures that resist denaturation and interfere with primer annealing. Secondary structures can also block the advance of DNA polymerase during the extension step, resulting in poor amplification of the desired products or in the amplification of shortened PCR products lacking the sequence containing the secondary structure (3)(8). …”
mentioning
confidence: 99%
“…Some methodologies involve protocols such as stepdown PCR, slowdown PCR, or PCR with multiple heat pulses during the extension phase (8, 9). Certain organic co-solvents such as DMSO, formamide, and ethylene glycol have been shown to facilitate DNA strand separation by disrupting base pairing, and other agents such as tetraalkylammonium (TAA) salts and betaine have also been used (10)(13); however, high concentrations of these additives inhibit DNA polymerase activity (14, 15).…”
mentioning
confidence: 99%